Preparation method of high-performance concrete anticorrosive paint and coating
By generating inorganic deposits such as TiO2, P2O5, and SiO2 on the concrete surface and cross-linking them with epoxy resin to form a film, a dual structure of embedded inorganic interface deposition and outer organic cross-linking is formed, which solves the problems of poor anti-corrosion effect and poor construction adaptability in the existing technology, and achieves long-term protection effect in high-salt and high-acid environments.
Patent Information
- Application Number
- CN202511287842.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-10
- Publication Date
- 2025-11-07
- Estimated Expiration
- 2045-09-10
AI Technical Summary
Existing concrete protection technologies are prone to failure in high-salt and high-acid environments, have limited anti-corrosion effects, have strict requirements on concrete moisture content, poor construction adaptability, and are difficult to meet the durability requirements for long service life and harsh environments.
A high-performance concrete anti-corrosion coating is adopted, which includes component A and component B. By introducing hydrolyzable titanate, phosphate and silicate, inorganic deposits such as TiO2, P2O5 and/or SiO2 are generated in situ on the concrete surface to form a dense interface layer. This layer is then cross-linked with the epoxy resin system to form a film, thus constructing a dual structure of embedded inorganic interface deposition and outer organic cross-linking.
It significantly improves the chemical bonding and interfacial stability between the coating and the substrate, provides excellent durability and barrier properties, is suitable for substrates with high humidity and high moisture content, extends the coating life, and is particularly suitable for infrastructure protection in high-salt and high-acid environments.
Smart Images

Figure FT_1
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the field of building materials and anti-corrosion technology, and particularly relates to a preparation method of a high-performance concrete anti-corrosion coating and coating. BACKGROUND
[0002] Concrete is one of the most widely used building materials at present, and is widely used in the fields of industry, transportation, energy and municipal engineering due to its high strength, convenient construction and low cost. However, due to the existence of pores and capillary channels inside, concrete is easily eroded by water, chloride, acid and alkali and other corrosive media during long-term service, resulting in performance degradation, structure damage and even failure. A large number of studies and engineering practices have shown that concrete corrosion not only causes steel corrosion and structure cracking, but also seriously shortens the service life of the structure, and often causes huge economic losses and safety hazards in harsh environments such as bridges, tunnels, dams, workshops, ports and salt chemical pools.
[0003] In order to delay the corrosion of concrete, the common protection methods at present mainly include two categories of permeable siloxane material treatment and organic coating covering. The protection mechanism of the former is to rely on the penetration of siloxane molecules into the pores of concrete, and the alkoxyl group is hydrolyzed under alkaline conditions and combined with the matrix to form a certain hydrophobic barrier, thereby reducing the porosity and water absorption. However, this method cannot completely seal the capillary channel, and the barrier effect on corrosive media is limited, and the protection effect obviously decreases in high salinity or strong acid environment, which is difficult to meet the use requirements in extreme conditions such as salt chemical industry and sewage treatment.
[0004] The organic coating forms an isolation film on the surface of the concrete to prevent the intrusion of external media, thereby prolonging the service life of the structure. Common systems include epoxy resin, polyurethane, acrylic resin, etc., which show good durability in neutral environment. However, this type of coating has high requirements for construction conditions, especially for the water content of the base material. The existing construction specification generally stipulates that the water content of concrete should be less than 6.0%, otherwise it is easy to cause the coating to have poor adhesion, bubbles and cracking, thereby reducing the protection performance. Since the concrete in actual engineering is often in a humid state, this limitation greatly reduces the construction efficiency and application range.
[0005] In addition, single organic coating also has the problems of insufficient weather resistance and rapid decline of barrier performance during long-term service. Especially in special working conditions with high salinity and significantly lower acidity than neutrality, such as salt chemical halogen production pool, part of sewage treatment device and chemical production site, the corrosion rate is much higher than that in ordinary marine environment, and conventional coating often fails in a short period of time. With the development of concrete structures towards large volume, long service life and harsh service environment, the existing protection technology cannot guarantee the service period, which has become a key bottleneck restricting the durability of engineering.
[0006] Therefore, it is urgent to develop a high-performance, environmentally friendly and construction-adaptable concrete anticorrosive coating, which can maintain good film-forming property under high water content of concrete and provide long-term effective protection under harsh conditions such as high salt and high acid, so as to meet the higher requirements of future infrastructure and industrial structures for durability and safety. SUMMARY
[0007] The present application aims at the problems of limited anticorrosive effect, strict requirement for water content of concrete and easy failure in high salt and high acid environment in the existing concrete protection technology, and provides a high-performance concrete anticorrosive coating and a preparation method of the coating, so as to realize the purposes of strong construction adaptability of the coating, long-lasting protection effect and effective extension of the service life of concrete structure in harsh environment.
[0008] To achieve the above purposes, the technical solutions adopted by the present application are as follows: The first aspect of the present application provides a high-performance concrete anticorrosive coating, which comprises A component and B component, wherein the A component comprises, by mass fraction, 100 parts of epoxy resin, 15-30 parts of composite solvent, 30-50 parts of organic solvent, 1-3 parts of dispersant, 1-3 parts of fumed silica and 0.5-2 parts of leveling agent; the B component comprises 15-25 parts of epoxy curing agent, 8-14 parts of conductive polymer dispersion liquid and 6-12 parts of organic solvent; wherein the composite solvent is prepared from one or more of orthotitanate, phosphate and orthosilicate and one or more of ester, ketone, alcohol, aromatic hydrocarbon, aliphatic hydrocarbon and ether organic solvent.
[0009] Preferably, the high-performance concrete anticorrosive coating comprises A component and B component, wherein the A component comprises, by mass fraction, 100 parts of epoxy resin, 20-25 parts of composite solvent, 35-45 parts of organic solvent, 1.5-2.5 parts of dispersant, 1.5-2.5 parts of fumed silica and 0.8-1.5 parts of leveling agent; the B component comprises 18-22 parts of epoxy curing agent, 10-13 parts of conductive polymer dispersion liquid and 8-11 parts of organic solvent; wherein the composite solvent is prepared from one or more of orthotitanate, phosphate and orthosilicate and one or more of ester, ketone, alcohol, aromatic hydrocarbon, aliphatic hydrocarbon and ether organic solvent.
[0010] Further, the mass fraction of one or more of orthotitanate, phosphate and orthosilicate in the composite solvent is 5.0%-100.0%, preferably 30%-80%, and more preferably 60%-70%.
[0011] Further, the composite solvent is prepared from one or more of orthotitanate, phosphate and orthosilicate and one or more of ester, ketone, alcohol, aromatic hydrocarbon, aliphatic hydrocarbon and ether organic solvent.
[0012] Further, the mass ratio of the orthotitanate, the phosphate and the orthosilicate is 1: (0.8-1.2): (0.8-1.2).
[0013] Further, the orthotitanate is one or more of tetraethyl orthotitanate, butyl orthotitanate and isopropyl orthotitanate; the phosphate is one or more of triethyl phosphate, tributyl phosphate and trimethyl phosphate; and the orthosilicate is one or more of tetraethyl orthosilicate, methyl orthosilicate and butyl orthosilicate.
[0014] In the present application, the orthotitanate, the phosphate and the orthosilicate are key functional additives in the coating formula. The orthotitanate has good surface activity and inorganic phase affinity, and can effectively improve the interfacial bonding capacity between inorganic fillers and organic resins in the coating, and improve the dispersion stability and film-forming compactness of the system. At the same time, part of the orthotitanate can also react with the hydroxyl groups on the surface of the substrate to enhance the adhesion of the coating to the concrete. The phosphate has excellent heat resistance, hydrolysis resistance and flame retardant properties, and also has certain surface tension adjusting ability, which can improve the flexibility and moisture and heat aging resistance of the coating film. The orthosilicate can form a dense three-dimensional cross-linked structure during curing, thereby improving the hydrophobicity, permeation resistance and weather resistance of the coating, especially in environments such as chloride ion penetration, high humidity and ultraviolet exposure, which can significantly delay aging and failure.
[0015] In the preferred technical solution of the present application, the above three types of ester compounds are used in combination to realize the interface synergy and functional superposition of organic-inorganic at the molecular level: the orthotitanate provides structural bonding and dispersion support, the phosphate provides flexibility and corrosion resistance, and the orthosilicate provides a dense network and a waterproof barrier, so that the coating has multiple performance indicators such as high adhesion, high compactness, corrosion resistance and permeation resistance, which is significantly better than a single functional component system, and gives the concrete coating the ability to serve stably for a long time in extreme working conditions such as high salt, high acid and high humidity.
[0016] Further, the organic solvent in the A component and the B component is one or more of alcohols, esters and ketones; for example, methanol, ethanol, propanol, n-butanol, ethyl acetate, butyl acetate, acetone, butanone and cyclohexanone.
[0017] Further, the dispersant is one or more of polycarboxylic acid, polyamide, block copolymer, sulfosuccinic acid ester or organic phosphonate dispersant; for example, 25736-86-1 polyethylene glycol methyl polyacrylate dispersant of Wuhan Gushun Chemical Co., Ltd., E-3910 polyamide dispersant of Shandong Huleng New Material Co., Ltd., and BYK163 block copolymer dispersant of BYK Germany.
[0018] Further, the leveling agent is one or more of acrylate, polyether modified silicone oil or fluorine modified polymer leveling agent; for example: RF-7106 acrylate leveling agent of Qingdao Shengshi New Material Co., Ltd., WE3221 polyether modified silicone leveling agent of BASF, SI-2041 fluorine modified acrylate leveling agent of Laizhang Shengbang Silicone Technology Co., Ltd.
[0019] Further, the epoxy curing agent is one or more of amine, low molecular weight polyamide, phenolic amine and imidazole; for example: small molecule organic amine such as ethylenediamine, diethylenetriamine, triethylenetetramine and pentanediamine; low molecular weight polyamide such as P203, 650 and 651; phenolic amine or cashew phenol modified phenolic amine such as T31, T33 and 1041; and alkylimidazole curing agent such as ethylimidazole.
[0020] Further, the conductive polymer dispersion liquid is anhydrous polyaniline dispersion liquid with a mass fraction of 10-30%.
[0021] The second aspect of the present application provides a preparation method of high-performance concrete anticorrosive coating, comprising the following steps: (1) mixing epoxy resin, composite solvent and organic solvent in the A component, stirring, then adding dispersant, fumed silica and leveling agent in sequence, continuing to stir, to obtain the A component; mixing epoxy curing agent, conductive polymer dispersion liquid and organic solvent in the B component, to obtain the B component; mixing the A component and the B component, then standing for 15-30 minutes, to obtain the anticorrosive coating; (2) cleaning the surface of the concrete substrate, coating the anticorrosive coating of step (1) on the surface of the concrete substrate, and controlling the coating thickness to be 200-600 μm; (3) curing the coating, to obtain the high-performance concrete anticorrosive coating.
[0022] Further, the curing temperature of step (3) is 20-30℃, and the curing time is 48-168 hours.
[0023] The coating of the present application forms a dense, firmly adhered and chemically bonded "interface dense layer" at the interface between the coating and the concrete substrate, which significantly blocks the penetration channels of corrosive media such as water, acid and salt, and improves the chemical stability and sealing property of the coating and the concrete interface.
[0024] At the same time, the external epoxy resin system is cross-linked into a film under the action of a curing agent, building a dense organic coating with good mechanical strength, wear resistance and chemical medium barrier ability. In this way, the coating structure presents a double structure of "inorganic interface deposition in the inner layer + organic cross-linked coating film in the outer layer": the former, like an inner lining, is embedded in the concrete micropores, enhancing the density and adhesion of the substrate, and the latter, like an outer shell, provides a physical barrier and anti-permeation function, both of which work together to achieve multi-dimensional protection of the concrete structure.
[0025] Compared with traditional coating systems, the dual-function composite protective layer not only has significantly improved corrosion resistance, but also has a longer service life and stronger interface stability, and is particularly suitable for concrete infrastructure in complex service environments such as high salt, high acid, high humidity, high temperature, etc., such as coastal structures, chemical plant floors, pools, water channels and other key protection scenarios.
[0026] Compared with the prior art, the present application has the following beneficial effects: 1. Strong adhesion and interface stability: By introducing hydrolyzable orthotitanate, phosphate and orthosilicate, inorganic deposits such as TiO2, P2O5 and / or SiO2 are generated in situ on the concrete surface, forming an "interface dense layer" that significantly enhances the chemical bonding force of the coating and the substrate, with adhesion far higher than that of traditional coatings and better interface stability.
[0027] 2. Excellent durability and barrier performance: The coating remains intact after long-term immersion in salt water, acid and base, and deionized water, showing good water resistance, salt resistance and chemical corrosion resistance, with significantly improved resistance to chloride ion penetration and electrochemical impedance, effectively blocking the intrusion of corrosive media.
[0028] 3. Suitable for high-humidity and high-water-content substrates: The coating has strong adaptability to the water content of concrete and can form a film on the surface of a substrate with a moisture content of more than 6%, solving the problem of the strong dependence of traditional epoxy coatings on dry conditions and significantly improving construction efficiency and applicability.
[0029] 4. Organic-inorganic composite structure synergistic protection: The inner inorganic deposition layer seals the concrete micropores, and the outer epoxy cross-linked film provides mechanical and chemical barriers, forming a "embedded + protected" dual protection system that significantly improves the long-term stability of the coating in extreme environments.
[0030] 5. Suitable for extreme corrosion environments: The coating remains intact after long-term use in harsh conditions such as high salt and high acid, far exceeding the service life of traditional coatings, and is particularly suitable for infrastructure protection in heavy corrosion areas such as coastal areas, salt chemical plants and sewage treatment.
[0031] 6. Simple construction, environment-friendly: the paint is a two-component system, which can be used after mixing, and is cured at room temperature without heating or special equipment. The solvent used is a conventional environmentally friendly organic solvent, meeting the requirements of green construction. BRIEF DESCRIPTION OF DRAWINGS
[0032] Figure 1 Corrosion comparison chart of the anti-corrosion coating prepared in Example 1 of the present application after one year in the extreme environment of a halogen pool. Among them, a: concrete surface coated with coating; b: bare concrete surface without coating. DETAILED DESCRIPTION
[0033] The technical solutions in the embodiments of the present application will be described below in a clear and complete manner. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those of ordinary skill in the art without creative labor fall within the scope of protection of the present application. In addition, it is worth noting that the raw materials involved in the present application are ordinary commercially available products unless otherwise specified. EMBODIMENT
[0034] The present embodiment provides a high-performance concrete anti-corrosion coating, comprising the following steps: (1) Preparation of composite solvent Take 66.67 g of tetraethyl orthotitanate, 66.67 g of triethyl phosphate and 66.66 g of tetraethyl orthosilicate, mix them evenly, then add 50.0 g of ethyl acetate and 50.0 g of butyl acetate, stir evenly to obtain a composite solvent.
[0035] (2) Preparation of component A In 100 g of E44 epoxy resin, add 22.5 g of the above composite solvent and 37.96 g of mixed organic solvent (a mixture of ethyl acetate and butyl acetate), stir evenly, then add 2.0 g of dispersant (BYK163 block copolymer dispersant), 2.0 g of fumed silica and 1.0 g of leveling agent (WE3221 polyether modified silicone) in turn, continue to stir evenly, and then grind and disperse to obtain component A.
[0036] (3) Preparation of component B In 30 g of T31 epoxy curing agent with an amine value of about 435, add 13.0 g of anhydrous polyaniline dispersion liquid with a mass fraction of 20%, and then add 12.15 g of mixed solvent (a mixture of ethanol and n-butanol), stir evenly to obtain component B.
[0037] (4) Mixing and construction of paint Take 60 g of component A and 20 g of component B, mix them evenly, and then stand for 15 minutes to obtain the anti-corrosion coating for construction.
[0038] The surface of the C80 concrete substrate to be treated is cleaned, free of dust, oil stains and visible water stains, and the above-mentioned coating is uniformly coated on the concrete surface in three coats by brushing, with the total thickness of the coating layer controlled at 300±40 μm.
[0039] (5) Coating curing The coated sample is placed in a room temperature (about 25°C) environment for curing for 168 hours to obtain a dense, uniform high-performance concrete anticorrosive coating. Example
[0040] The present embodiment provides a high-performance concrete anticorrosive coating, comprising the following steps: (1) Preparation of a composite solvent Take 200.0 g of tetraethyl orthotitanate, and add 50.0 g of ethyl acetate and 50.0 g of butyl acetate in sequence, and stir until uniform to obtain a composite solvent.
[0041] (2) Preparation of component A In 100 g of E44 epoxy resin, add 22.5 g of the above-mentioned composite solvent and 37.33 g of mixed organic solvent (a mixture of ethyl acetate and butyl acetate), stir until uniform, then add 2.0 g of dispersant (BYK163 block copolymer dispersant), 2.0 g of fumed silica and 1.0 g of leveling agent (SI-2041 fluorine-modified acrylate leveling agent) in sequence, continue to stir until uniform and grind and disperse to obtain component A.
[0042] (3) Preparation of component B In 30 g of T31 epoxy curing agent with an amine value of about 435, add 13.0 g of anhydrous polyaniline dispersion liquid with a mass fraction of 20%, and then add 11.94 g of mixed solvent (a mixture of ethanol and n-butanol), and stir until uniform to obtain component B.
[0043] (4) Coating mixing and construction Take 60 g of component A and 20 g of component B, mix them uniformly, and then stand for 15 minutes to obtain the anticorrosive coating for construction.
[0044] The surface of the C80 concrete substrate to be treated is cleaned, free of dust, oil stains and visible water stains, and the above-mentioned coating is uniformly coated on the concrete surface in three coats by brushing, with the total thickness of the coating layer controlled at 300±40 μm.
[0045] (5) Coating curing The coated sample is placed in a room temperature (about 25°C) environment for curing for 168 hours to obtain a dense, uniform high-performance concrete anticorrosive coating. Example
[0046] The embodiment provides a high-performance concrete anticorrosive coating, including the following steps: (1) Preparation of a composite solvent Take 200.0 g of triethyl phosphate, and then add 50.0 g of ethyl acetate and 50.0 g of butyl acetate, and stir until uniform, to obtain a composite solvent.
[0047] (2) Preparation of component A In 100 g of E44 epoxy resin, 22.5 g of the composite solvent and 40.29 g of mixed organic solvent (a mixture of ethyl acetate and butyl acetate) are added, and after uniform stirring, 2.0 g of dispersant (E-3910 polyamide dispersant), 2.0 g of fumed silica and 1.0 g of leveling agent (SI-2041 fluorine-modified acrylate leveling agent) are sequentially added, and uniform stirring and grinding and dispersion are continued, to obtain component A.
[0048] (3) Preparation of component B In 30 g of T31 epoxy curing agent with an amine value of about 435, 13.0 g of anhydrous polyaniline dispersion liquid with a mass fraction of 20% is added, and then 12.93 g of mixed solvent (a mixture of ethanol and n-butanol) is added, and uniform stirring is performed, to obtain component B.
[0049] (4) Mixing and construction of the coating After 60 g of component A and 20 g of component B are uniformly mixed, standing for 15 minutes, an anticorrosive coating for construction is obtained.
[0050] The surface of the cleaned C80 concrete substrate is cleaned and dried, and three layers are uniformly constructed by brushing, and the final coating thickness is controlled to be 300±40 μm.
[0051] (5) Curing of the coating The coated concrete sample is placed in a room temperature (25±2℃) condition for curing for 168 hours, to obtain a dense and uniform high-performance concrete anticorrosive coating. Embodiment
[0052] The embodiment provides a high-performance concrete anticorrosive coating, including the following steps: (1) Preparation of a composite solvent Take 200.0 g of tetraethyl orthosilicate, and then add 50.0 g of ethyl acetate and 50.0 g of butyl acetate, and stir until uniform, to obtain a composite solvent.
[0053] (2) Preparation of component A In 100 g of E44 epoxy resin, 22.5 g of the above-mentioned composite solvent and 36.26 g of mixed organic solvent (a mixture of ethyl acetate and butyl acetate) were added, and after stirring uniformly, 2.0 g of dispersant (E-3910 polyamide dispersant), 2.0 g of fumed silica and 1.0 g of leveling agent (RF-7106 acrylate leveling agent) were added in turn, and uniform stirring and grinding dispersion were continued to obtain the A component.
[0054] (3) Preparation of the B component In 30 g of T31 epoxy curing agent with an amine value of about 435, 13.0 g of anhydrous polyaniline dispersion liquid with a mass fraction of 20% was added, and 11.59 g of mixed solvent (a mixture of ethanol and n-butanol) was added, and stirred uniformly to obtain the B component.
[0055] (4) Mixing and application of the coating After 60 g of the A component and 20 g of the B component were mixed uniformly, they were left to stand for 15 minutes to obtain the anticorrosive coating for application.
[0056] The pretreated clean C80 concrete substrate surface was cleaned and dried, and three coats were applied by brushing, with the final coating thickness controlled at 300±40 μm.
[0057] (5) Curing of the coating The coated concrete sample was placed in a room temperature (25±2℃) condition for curing for 168 hours to obtain a dense, uniform high-performance concrete anticorrosive coating.
[0058] This comparative example provides a concrete anticorrosive coating, which differs from Example 1 in that step (2) is: 22.5 g of a mixed solution of ethyl acetate and butyl acetate (mass ratio 1:1) is used to replace the composite solvent in Example 1 for the preparation of the A component, and the remaining components and operation steps are the same as in Example 1.
[0059] This comparative example provides a concrete anticorrosive coating, which differs from Example 1 in that step (1) is: 100 g of KH560 is used to replace the composite solvent in Example 1 to prepare the A component, and the remaining components and operation steps are the same as in Example 1.
[0060] This comparative example provides a concrete anticorrosive coating, which differs from Example 1 in that step (1) is: 100 g of TiO2 (anatase type) and 50 g of talc are used to replace the composite solvent in Example 1 to prepare the A component, and the remaining components and operation steps are the same as in Example 1.
[0061] Test samples: Anticorrosive coatings prepared by Examples 1-4 and Comparative Examples 1-3.
[0062] Test method: Water resistance, salt water resistance, alkali resistance and acid resistance test (GB / T 1763-1989): by immersing the sample in deionized water, 5.0% sodium chloride solution, 5.0% sodium hydroxide solution and 5.0% hydrochloric acid solution at room temperature respectively, to a certain time (hours) to observe the surface change of the coating, the coating is complete, no hollow, crack.
[0063] Chloride ion permeability test (GB / T50082-2009): using the electric flux method, by measuring the amount of chloride ion permeation per unit time, to evaluate the water and salt resistance of the coating, the unit is mg / (cm 2 ·d).
[0064] Coating impedance: using electrochemical impedance spectroscopy (EIS) measurement method, in a three-electrode system with 10 mV perturbation voltage, frequency range 10 5 -10 -2 Hz scanning, recording the Nyquist plot of the coating and calculating the equivalent circuit impedance value, the unit is Ω·cm 2 .
[0065] Adhesion test: pull off the sample by pull-off method, if the failure position is inside the concrete (pull off the concrete), it indicates that the adhesion is greater than the concrete strength; if it occurs at the coating / substrate interface, calculate the adhesion strength with the maximum pulling force required for failure, the unit is MPa.
[0066] The test results are shown in Tables 1 and 2.
[0067] Table 1 Performance test results Table 2 Performance test results From the test results in Tables 1 and 2, it can be seen that the coatings prepared in Examples 1-4 all exhibit excellent performance in water resistance, salt water resistance, alkali resistance and acid resistance, especially Example 1 performs the most outstanding in all tests, with corrosion resistance time exceeding 10,000 hours, chloride ion permeability as low as 1.1 x 10 - 5 mg / (cm 2 ·d), coating impedance as high as 3.1 x 10 10 Ω·cm 2 , adhesion reaching 3.1 MPa, showing excellent protection effect. This indicates that the synergistic effect of orthotitanate, phosphate and orthosilicate in the complex solvent significantly enhances the compactness, interfacial bonding strength and resistance to medium penetration of the coating.
[0068] In comparison, Comparative Example 1 only uses a common mixed solvent, lacks the hydrolytic deposition of functional esters, and results in a decrease in coating barrier properties, adhesion, and a significantly poorer resistance to chloride ion penetration than the examples; Comparative Example 2 uses a KH560 silane coupling agent instead of a composite solvent, has a certain coupling effect, but cannot form a multi-element inorganic deposition layer, and the interface sealing and corrosion resistance are still not as good as the examples; Comparative Example 3 directly uses inorganic fillers such as TiO2 and talc, lacks an in-situ reaction film formation mechanism, the coating has weak adhesion to the substrate, and the impedance and adhesion are both low, and the overall protection effect is the worst.
[0069] To further verify the use stability of the high-performance concrete anticorrosive coating in extreme environments, the anticorrosive coating prepared in Example 1 was applied to the surface of a concrete body of a halogen pool of Shandong Haohua Group, and was exposed and placed under natural conditions for one year. The salinity of the brine in the halogen pool is much higher than that of ordinary seawater (the salt content of seawater is about 3.5%), is in a long-term near-saturation state (the salt content is as high as 26.5%), and has a higher acidity, with a pH of about 2.0, and even lower than 2.0 in some periods, and the corrosion intensity is much higher than that of a typical marine environment. The test results are shown in Figure a and b. Figure 1 The results further show that the anticorrosive coating has excellent long-term protection ability in a high-salt and high-acid harsh environment.
[0070] Finally, it should be noted that the above content is only used to illustrate the technical solutions of the present application, and is not a limitation on the protection scope of the present application. Simple modifications or equivalent replacements of the technical solutions of the present application made by those skilled in the art do not deviate from the essence and scope of the technical solutions of the present application.
Claims
1. A high performance concrete corrosion protection coating comprising a part A and a part B, the part A comprising, by mass parts: Epoxy resin 100 parts, composite solvent 15-30 parts, organic solvent 30-50 parts, dispersant 1-3 parts, fumed silica 1-3 parts, leveling agent 0.5-2 parts; B component includes epoxy curing agent 15-25 parts, conductive polymer dispersion liquid 8-14 parts, organic solvent 6-12 parts; wherein, the composite solvent is prepared by one or more of orthotitanate, phosphate ester, orthosilicate and one or more of ester, ketone, alcohol, aromatic hydrocarbon, aliphatic hydrocarbon, ether organic solvent.
2. The high performance concrete corrosion protection coating of claim 1, wherein: A component and B component, by mass parts, A component includes: epoxy resin 100 parts, composite solvent 20-25 parts, organic solvent 35-45 parts, dispersant 1.5-2.5 parts, fumed silica 1.5-2.5 parts, leveling agent 0.8-1.5 parts; B component includes epoxy curing agent 18-22 parts, conductive polymer dispersion liquid 10-13 parts, organic solvent 8-11 parts; wherein, the composite solvent is prepared by one or more of orthotitanate, phosphate ester, orthosilicate and one or more of ester, ketone, alcohol, aromatic hydrocarbon, aliphatic hydrocarbon, ether organic solvent.
3. The high performance concrete corrosion protection coating of claim 1 or 2, wherein: The mass ratio of one or more of orthotitanate, phosphate ester and orthosilicate in the composite solvent is 5.0%-100.0%, preferably 30%-80%, more preferably 60%-70%.
4. The high performance concrete corrosion protective coating of claim 1 or 2, wherein: The composite solvent is prepared by one or more of orthotitanate, phosphate ester and orthosilicate and one or more of ester, ketone, alcohol, aromatic hydrocarbon, aliphatic hydrocarbon, ether organic solvent; wherein the mass ratio of orthotitanate, phosphate ester and orthosilicate is 1: (0.8-1.2): (0.8-1.2).
5. The high performance concrete corrosion protective coating of claim 1 or 2, wherein: The orthotitanate is one or more of tetraethyl orthotitanate, butyl orthotitanate, isopropyl orthotitanate; the phosphate ester is one or more of triethyl phosphate, tributyl phosphate, trimethyl phosphate; the orthosilicate is one or more of tetraethyl orthosilicate, methyl orthosilicate, butyl orthosilicate.
6. The high performance concrete corrosion protective coating of claim 1 or 2, wherein: The organic solvent in the A component and B component is one or more of alcohol, ester, ketone; the dispersant is one or more of polycarboxylic acid, polyamide, block copolymer, sulfosuccinic acid ester or organic phosphonate salt dispersant.
7. The high performance concrete corrosion protective coating of claim 1 or 2, wherein: The leveling agent is one or more of acrylate, polyether modified silicone oil or fluorine modified polymer; the epoxy curing agent is one or more of amine, low molecular weight polyamide, phenolic amine, imidazole.
8. The high performance concrete corrosion protective coating of claim 1 or 2, wherein: The conductive polymer dispersion liquid is anhydrous polyaniline dispersion liquid with a mass fraction of 10-30%.
9. The method for preparing a coating of high-performance concrete anticorrosive paint according to any one of claims 1-8, comprising the following steps: (1) mixing the epoxy resin, composite solvent and organic solvent in the A component, stirring, then sequentially adding the dispersant, fumed silica and leveling agent, continuing to stir, to obtain the A component; mixing the epoxy curing agent, conductive polymer dispersion liquid and organic solvent in the B component to obtain the B component; mixing the A component and the B component and standing for 15-30 minutes to obtain the anticorrosive paint; (2) cleaning the surface of the concrete substrate, and applying the anticorrosive coating of step (1) to the surface of the concrete substrate, with the coating thickness controlled to be 200-600 μm; (3) curing the coating to obtain a high-performance concrete anticorrosive coating.
10. The method of claim 9, wherein: The curing temperature of step (3) is 20-30°C, and the curing time is 48-168 hours.
Citation Information
Patent Citations
Low-surface treatment moisture cured heavy anti-corrosion coating
CN101824265A
Coating composition as well as preparation method and application thereof
CN115820112A
Chromium-free zinc-aluminum coating material for high-strength fastener and coating method of chromium-free zinc-aluminum coating material
CN116875170A
Solvent-free organosilicone-epoxy fireproof coating for steel structure as well as preparation method and application of solvent-free organosilicone-epoxy fireproof coating
CN118599400A
Durable modified epoxy resin composite coating and preparation method thereof
CN119978946A
Cited By
Benzene-free diluent for coating and preparation method of benzene-free diluent
CN121319691A
A benzene-free diluent for paints and a method for preparing the same
CN121319691B